SISTEM MONITORING PADA RANCANG BANGUN MESIN PENGEMASAN BENDA DENGAN SISTEM PNEUMATIK BERBASIS PLC DAN HMI - Pratama, Muhammad David; Sjahrul, Yurika; S, Sarip udin; Saripudin S (Jurnal TEDC, 2024)
The desire to work more effectively and efficiently makes humans continue to innovate to create technology that can facilitate human work in all fields and types of work, one of which is the industrial field. Technological advances in the industrial sector are better known as the industrial revolution. One of the impacts of the industrial revolution that continues to grow rapidly is the operation of industrial machines, most of which are operated automatically. Control technology that can make machines work automatically is a Programmable Logic Controller (PLC). PLC is a computer designed to control a machine or system. One of the uses of PLC in the industrial world is on a packing machine using box. In the packaging machine, the PLC acts as an actuator controller, the actuator used is a solenoid valve to speed up the packaging process automatically. In addition to controlling the actuator, PLC can also monitor this goods packaging machine remotely using the Human Machine Interface. From the results of the tests carried out, it is found that the system that has been made can work properly, this can be seen in the HMI which can operate the system and when there is damage to the system, the history alarm will turn on so that it can facilitate the system repair process.